Stressor and Coping with Stress on Bilingual Madrasah Aliyah Teachers in Sidoarjo - Laila Nur Izzati; Sofyan Anif; Djalal Fuadi (Budapest International Research and Critics University, 2023)
Teachers as figures who interact and deal directly with students are required to have good qualifications and competence. The teacher plays an important role in education in the form of being indispensable in shaping the character of students, being a role model for students, fostering enthusiasm for student learning and also increasing creativity in learning. Jobs as teachers are more prone to experiencing stress at work. This study aims to determine stressors and stress coping on MA Bilingual Sidoarjo teachers. This study used a qualitative descriptive approach using three sources, namely the head of the madrasah, deputy head of curriculum and deputy head of student affairs. The results of this study stated that the stressors experienced by Ma Bilingual Sidoarjo teachers were due to students' bad behavior, differences in character, and workload. 1) When the teacher feels pressured by the student's bad behavior, what the teacher does to minimize the pressure is to approach the student and the student's guardian. 2) When stressors are in the form of differences in character, what is done is a coordination meeting with the leadership so that mutual agreement can reach a consensus. 3) Teacher workload that causes work stress in teachers can be overcome by improving communication, and training according to their field and evaluation meetings. That way, coping stress is applied by the Sidoarjo Bilingual MA teacher using a strategy that focuses on the problem.